PENERAPAN METODE ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS MATERI ANNOUNCEMENT PADA SISWA KELAS X MIPA 1 SMA NEGERI 1 GIRIMARTO SEMESTER 2 TAHUN PELAJARAN 2021/2022 - suwati wati (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2023)
The research is done to know the increasing of studying result of students class X MIPA 1 SMA Negeri 1 Girimarto, Wonogiri, Central Java, By Implementation Role Playing Method of English lesson Material of Announcement. This Research is Class Action research that done at least 2 cycles. Subject of research  are 36 students of class X MIPA 1 SMA N 1 Girimarto. Technic of submitting data of students studying result by studying result test. Technic of  data analysis is kuantitatif data analysis, It is the average of test value of student studying. The result of this  research increase studying result of students class X MIPA 1 SMA Negeri 1 Girimarto at Semester 2 2021/2022 by implementation of Role playing method that proved by increasing the average value of the students studying result and the completeness of students learning.  The increasing of students results at pre cycle  showed  the student average value  is 56,26 or 13,89 %  students had completed. Cycle 1 of studying Result of students  have not reached  minimum completed criteria,  41,67 %, with the class average value 66,67 % that still under KKM value >_ 70 and completeness prosentase KKM >_ 70 %.  At cycle 2 the result of students studying had reached KKM ( Minimum Completeness Criteria ) 86,11 % with the class average  value 83,61 and already beyond  KKM value. From this research data can be concluded that the implementation of Role Playing Method had success increased  result studying of English the material of Announcement so worthy to applied at SMA Negeri 1 GirimartoWonogiri, Central Java.